2006
DOI: 10.1117/12.657322
|View full text |Cite
|
Sign up to set email alerts
|

Evanescent wave imaging in optical lithography

Abstract: New applications of evanescent imaging for microlithography are introduced. The use of evanescent wave lithography (EWL) has been employed for 26nm resolution at 1.85NA using a 193nm ArF excimer laser wavelength to record images in a photoresist with a refractive index of 1.71. Additionally, a photomask enhancement effect is described using evanescent wave assist features (EWAF) to take advantage of the coupling of the evanescent energy bound at the substrate-absorber surface, enhancing the transmission of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Prior work with EWAFs has focused on near-field enhancement of intensity at an aperture 1 . Expanding on these ideas, the enhancement effect is investigated more thoroughly and propagated to the far field.…”
Section: Evanescent Wave Enhancement Effectmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior work with EWAFs has focused on near-field enhancement of intensity at an aperture 1 . Expanding on these ideas, the enhancement effect is investigated more thoroughly and propagated to the far field.…”
Section: Evanescent Wave Enhancement Effectmentioning
confidence: 99%
“…The sub-wavelength grooves have been referred to as Evanescent Wave Assist Features, or EWAFs, since their primary purpose in the lithographic scope is to "assist" the aperture which they surround 1 . Previous work has demonstrated that these gratings, buried under the mask absorber, have the ability to enhance or inhibit the intensity at the center of a slit or contact.…”
Section: Evanescent Field Of Sub-wavelength Featuresmentioning
confidence: 99%
See 3 more Smart Citations